Pola Komunikasi Interpersonal Siswa SMAN Sidikalang Terhadap Kecanduan Bermain Game Mobile Legend - Afif Eido Pemanta Berampu; M. Yoserizal Saragih (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This research aims to determine the interpersonal communication patterns of SMAN 1 Sidikalang students regarding their addiction to playing Mobile Legends games. This research uses a qualitative descriptive method. This research is a field study. The data in this research comes from primary data obtained directly through direct findings in the research area such as the results of interviews and observations. This research data also comes from secondary data obtained through literature that relates to the research context such as journal articles and books. Data collection techniques in this research used semi-structured interviews and non-participant observation. Data analysis in this research was carried out by reducing, presenting, and then verifying the research data. The results of this research show that the interpersonal communication approach applied by teachers at SMA Negeri 1 Sidikalang is very focused on creating positive relationships with students. They listen attentively, show genuine interest, and avoid unnecessary interruptions. The body language they use supports a positive atmosphere, and simple language creates a comfortable environment. Teachers give praise to increase students' self-confidence and provide criticism wisely. They also demonstrate self-control and emotional maturity, helping students overcome gaming addiction problems. All of these approaches aim to create positive interpersonal relationships and provide important support in student development.